Application and enlightenment of mobile hospital in medical support for sports event - Jia, Bo; Zhang, Jian; Zhang, Ang; Zhu, Jiaqi; Sui, Mengyun; Xue, Long (Frontiers in Public Health, 2025)
With the vigorous development of sports events, the rising medical demand during the events has brought a heavy burden to urban emergency medical services. On the other hand, mobile hospitals, featuring strong mobility, high environmental adaptability, rapid deployment, and comprehensive functions, have shown great application value. This study provides an analysis of the unique advantages of mobile hospitals in rapid response and deployment, provision of on-site comprehensive medical services. Through literature review of the application of mobile hospital, the observation of mobile hospitals in the 2024 Tour Shanghai New City Cycling Race and the 2024 Shanghai Marathon, it is found that in sports events involving complex races such as cross-administrative regions and multi-stage races, mobile hospitals have significant application advantages, especially in improving the overall level of medical security of the race and significantly reducing the workload of emergency medical treatment. It shows great development potential.